KRITIK SOSIAL DALAM CERPEN PILIHAN KOMPAS 2014 DAN IMPLIKASINYA DALAM PEMBELAJARAN - Sastra, Yola; Thahar, Harris Effendi; Abdurahman, Abdurahman (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ This article was written that has purpose to describe the kind of social critic in the Cerpen Pilihan Kompas 2014. The research is a qualitative study using descriptive methods. Sources of data in this study is the short stories contained in the book of Cerpen Pilihan Kompas 2014, published by Kompas, Jakarta, second edition, August 2015. Social criticism found in this study, namely (1) the problem of poverty, (2) the problem of evil, (3) the problem of disorganization family, (4) problems young people in modern society, (5) the violation of the norms of society, (6) problems of population, (7) environmental problems, (8) the issue of religion and belief, and (9) the problem of bureaucracy.Â Kata kunci: kritik sosial, cerpen, kualitatif, deskriptif